Methodological approach to evaluate interactive behaviors in team games: an example in handball - Prudente, J.; Garganta, J.; Anguera, M. T. (Proceedings of the 7th International Conference on Methods and Techniques in Behavioral Research, 2010)
In this paper we describe a method to evaluate interactive behaviors in Team Games, most precisely goalkeeper interaction with defenders. The aim of this study is to understand the performance of a handball goalkeeper, not only by the results of their own actions, but by integrating in the model the interactive actions between goalkeeper and defenders. The requirements of observational methodology are observed to gather data and we used sequential analysis and polar coordinates techniques to analyze data. The data are gathered from a natural environment where players have their behaviors, i.e., from handball matches in high level competitions context. Using an observational tool specially created and validated by an expert panel, the data was registered in a sequential way to make possible the sequential analysis with lags, prospective and retrospectively made. The results show the goalkeeper performance is significantly associated with defenders actions.